2010
DOI: 10.1111/j.1475-6773.2010.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Patient Activation Measure among Multimorbid Older Adults

Abstract: Objectives The Patient Activation Measure (PAM) quantifies the extent to which people are informed about and involved in their health care. Objectives were to determine the psychometric properties of PAM among multi-morbid older adults and evaluate a theoretical, four-stage model of patient activation. Methods A cross-sectional analysis was used to assess the psychometric properties of PAM. Internal consistency was assessed using Cronbach’s alpha. Construct validity was evaluated using general linear modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
159
3
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(181 citation statements)
references
References 30 publications
(49 reference statements)
12
159
3
7
Order By: Relevance
“…eye examinations for people with diabetes, keeping diary of blood pressure readings), and control of chronic illness (e.g. HbA1c control, fewer hospitalizations) 13,14,[16][17][18][19][20] . Many of the studies are limited, however, by reliance upon self-reported health outcomes and use of relatively small samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…eye examinations for people with diabetes, keeping diary of blood pressure readings), and control of chronic illness (e.g. HbA1c control, fewer hospitalizations) 13,14,[16][17][18][19][20] . Many of the studies are limited, however, by reliance upon self-reported health outcomes and use of relatively small samples.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found patient activation to be a valid measure in a number of population subgroups (e.g. Latinos, uninsured, older adults with multiple chronic conditions) [14][15][16] . This is the first examination of whether the relationships between patient activation and health-related outcomes differ across SES strata.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that psychometrically, the PAM 13 has stronger and more detailed all round validity in demonstrating clear face, content, construct and criterion validity and psychometric reliability across populations (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). A large body of evidence therefore demonstrates that the PAM-13 is a valid, reliable and clinically useful measure of patient activation that can be used across diverse cultures and patient groups.…”
Section: Limitations Of the Promsmentioning
confidence: 99%
“…The PAM 13, a short-form version of the PAM 22, has been more extensively examined for use in additional populations and languages (14) . It offers strong psychometric evidence in people living with long term conditions (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The PAM; specifically the PAM-13, possesses a large body of evidence that supports its strong psychometric properties across diverse cultures and patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Psychological distress was analyzed as a dichotomous variable where scores of 13 or higher indicated the presence of psychological distress; patient activation was analyzed as a continuous variable. We also collected covariables at baseline to describe patient characteristics: (1) socioeconomic data (age, sex, marital status, education, occupation, economic status with family income, and perception of his/her economic situation); (2) health literacy, measured with the Newest Vital Sign (NVS) 30 ; (3) mental health, measured with the Hospital Anxiety and Depression Scale (HADS) 31,32 ; and (4) multimorbidity, measured with the Disease Burden Morbidity Assessment (DBMA).…”
Section: Quantitative Data Collection and Analysismentioning
confidence: 99%